Wybrane elementy relacji państwo-przedsiębiorca w odniesieniu do pomocy publicznej - Dobaczewska, Anna (Selected Items of The Country-Entrepreneur Relationships Regarding State Aid, 2008)
The Polish law of state aid reflects the EU regulations on the same subject. However some aspects of the relationships between the public authorities and entrepreneurs required harmonization. Two main legal acts dealing with the harmonization of the Polish law with the EU directives are: the Act on Procedures of Assigning and Monitoring of Public Aid for Entrepreneurs from 2004 and the Act on Transparency of Fiscal Relationships between the Public Authorities and Public Entrepreneurs and some other Entrepreneurs from 2006. As the second one has just come into force, we will have to wait for its actual results. But it is already expected that it will enforce the existence of a transparent and effective system of state aid. Meanwhile, notwithstanding numerous reporting obligations of all participants of the procedures regulated in both legal acts we experience a lack of a clear, homogeneous system which could reflect in more efficient and economic disbursement of public funds. Such a system should have as a consequence economic growth and better employment figures. The establishment of all efficient system means also more funds on horizontal aid and more indirect forms of state aid like preferential credits and guarantees instead of subsidies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 135-143